1997
DOI: 10.3109/15563659709043367
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Multicenter Evaluation of Tramadol Exposure

Abstract: This study suggests significant neurologic toxicity from tramadol overdose. Serious cardiovascular toxicity was not seen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
133
2
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(142 citation statements)
references
References 6 publications
6
133
2
1
Order By: Relevance
“…Young males were involved more frequently than females, which is in agreement with other studies in Iran and other countries [5,9,22]. The results show that ingestion of tramadol was the only route of intoxication.…”
Section: Discussionsupporting
confidence: 91%
“…Young males were involved more frequently than females, which is in agreement with other studies in Iran and other countries [5,9,22]. The results show that ingestion of tramadol was the only route of intoxication.…”
Section: Discussionsupporting
confidence: 91%
“…10 The toxic reaction was brief and self-limited, severe cardiovascular toxicity, such as hypotension or arrhythmias, was not seen and general supportive therapy appeared to be sufficient in managing these cases of overdose. 10 With a 5 mg·kg -1 loading dose, not exceeding 500 mg, we did not observe any serious adverse events. Conversely, intraoperative loading doses less than 1.25 mg·kg -1 appear of little benefit because of lack of analgesia in the PACU.…”
Section: Me Et Th Ho Od Ds S Following Approval By the Hospital's Rmentioning
confidence: 99%
“…We did not use doses greater than 5 mg·kg -1 in the design of this study, based on the report by Spiller et al 10 In a prospective multi-centre evaluation of tramadol, they reported 87 cases of tramadol intoxication in which 500 mg tramadol was the lowest dose associated with seizure, tachycardia, hypertension or agitation while 800 mg was the lowest dose associated with coma and respiratory depression. 10 The toxic reaction was brief and self-limited, severe cardiovascular toxicity, such as hypotension or arrhythmias, was not seen and general supportive therapy appeared to be sufficient in managing these cases of overdose.…”
Section: Me Et Th Ho Od Ds S Following Approval By the Hospital's Rmentioning
confidence: 99%
“…However, tramadol toxicity may be underestimated. Some non-lethal cases of respiratory depression, seizures, and serotonin syndrome have been reported with tramadol (1)(2). Several deaths have also been reported when tramadol was ingested alone in overdose (3)(4)(5), or when it was ingested with others drugs (6)(7)(8), particularly with central nervous system (CNS) depressants like benzodiazepine (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%